2022
DOI: 10.3389/fmars.2022.959366
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of juvenile leatherback turtles from different Caribbean nesting beaches: A model study

Abstract: The Northwest Atlantic (NWA) leatherback turtle (Dermochelys coriacea) subpopulation was recently classified as endangered. It nests in the Wider Caribbean Region and includes five genetic stocks, all declining, albeit at different rates. The causes of decline are multiple and difficult to identify based on annual nest counts which integrate the effects of multiple stressors over the entire life history. Demographic models, however, show that survival during the juvenile pelagic stage is the main factor modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…One possibility is that Puerto Rico is relatively remote from other bioregions except NSA and is isolated from that bioregion by the Caribbean Current, which flows westward, away from Puerto Rico. The one species inhabiting Puerto Rico, K. hermaphroditus, also inhabits the Lesser Antilles (Berbel-Filho et al, 2022), suggesting it dispersed along the Antillean Current from north-eastern South America, a pattern seen in juvenile sea turtles (Gaspar et al, 2022), but not in other freshwater fishes.…”
Section: (D) Summary Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that Puerto Rico is relatively remote from other bioregions except NSA and is isolated from that bioregion by the Caribbean Current, which flows westward, away from Puerto Rico. The one species inhabiting Puerto Rico, K. hermaphroditus, also inhabits the Lesser Antilles (Berbel-Filho et al, 2022), suggesting it dispersed along the Antillean Current from north-eastern South America, a pattern seen in juvenile sea turtles (Gaspar et al, 2022), but not in other freshwater fishes.…”
Section: (D) Summary Discussionmentioning
confidence: 99%
“…This directed outflow from the Gulf of México to the Straits of Florida (Guertin, Missimer & McNeill, 2000) and, combined with narrowing of the Central American seaway [Late Oligocene (Montes et al ., 2012; McGirr, Seton & Williams, 2021)], to establish the Caribbean–Loop Current System (Hübscher et al ., 2023). This system served as a dispersal avenue from northern South America to the Bahamas, with Central America, North America, and Cuba as points in between (Gaspar, Candela & Shillinger, 2022). Also in the Oligocene, uplift of the Andes Mountains created a continental, subAndean river system that discharged into the Caribbean from north‐western South America (Hoorn et al ., 2010; Wesselingh & Hoorn, 2011).…”
Section: Hypotheses Of Greater Antillean Immigrationsmentioning
confidence: 99%
“…This directed outflow from the Gulf of México to the Straits of Florida (Guertin, Missimer, & McNeill, 2000) and, combined with narrowing of the Central American seaway (Late Oligocene, Montes et al, 2012; McGirr, Seton, & Williams, 2021), to establish the Caribbean-Loop Current system (Hübscher et al, 2023). This system serves as a dispersal avenue from northern South America to the Bahamas, with Central America, North America, and Cuba as points in between (Gaspar et al, 2022). Also in the Oligocene, uplift of the Andes Mountains created a continental, subandean river system that discharged into the Caribbean from north-western South America (Hoorn et al, 2010; Wesselingh & Hoorn, 2011).…”
Section: Hypotheses Of Greater Antillean Immigrationsmentioning
confidence: 99%
“…Island immigration is dated 0.5-0.1 Ma (Tatarenkov et al, 2017). This species has a unique distribution pattern including the Lesser Antilles and Puerto Rico (Berbel-Filho et al, 2022), suggesting dispersal via the Antilles Current, as observed in juvenile leatherback turtles Dermochelys coriacea (Gaspar, Candela, & Shillinger, 2022). However, a population of K. hermaphroditus in EP-CB bioregions indicates the species also either dispersed via the Caribbean Current to the Panamá-Columbia Gyre or along the northern coast of South America.…”
Section: Synthetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation